2015
DOI: 10.1021/acs.jced.5b00198
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Sound Speed, and Viscosities of Some Amino Acids with Aqueous Tetra-Butyl Ammonium Iodide Solutions at Different Temperatures

Abstract: Apparent molar volumes (V ⌀ ), apparent molar isentropic compression (K ⌀,s ), and viscosity B coefficient of glycine, L-alanine, and L-valine in (0.01 and 0.03) mol·kg −1 aqueous tetrabutyl ammonium iodide (TBAI) solutions have been determined at temperatures (288.15, 293.15, 298.15, 303.15, and 308.15) K from their experimental density, ultrasonic speed, and flow time measurements, respectively. Partial molar volumes (V ⌀ 0 ) and partial molar isentropic compression (K ⌀,s 0 ) have been determined from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The calculated values of E φ 0 at T = 288.15–308.15 K are given in Table S2 in Supporting Information. E φ 0 was an important indicator of solute–solvent interactions. These E φ 0 values were also employed in interpreting the structure making or breaking properties of various solutes. Table S2 in Supporting Information shows that the E φ 0 values were positive, which indicates that the partial molar volumes increased with the increase of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculated values of E φ 0 at T = 288.15–308.15 K are given in Table S2 in Supporting Information. E φ 0 was an important indicator of solute–solvent interactions. These E φ 0 values were also employed in interpreting the structure making or breaking properties of various solutes. Table S2 in Supporting Information shows that the E φ 0 values were positive, which indicates that the partial molar volumes increased with the increase of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The E φ 0 values decreased with an increase in temperature. This may be attributed to the fact that molecular motions become fast through enhancement in temperature and the difference in water structure between solvation shell and bulk water become smaller and, consequently, the corresponding effect from the overlap of solvation shells become weaker. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salt effects on water have been most commonly described in terms of their chaotropicity or kosmotropicity. Tetra- n -alkylammonium salts (R 4 NBr, R = CH 3 , C 2 H 5 ) are a separate class of electrolytes due to their unusual properties in solutions, apparently caused by their large size hydrophobic alkyl chains. Tetra- n -alkylammonium halides destabilize lysozyme by interacting with the exposed hydrophobic groups of the denatured state and simultaneously weakening the hydrophobic interactions between the nonpolar groups of the protein. It has been reported that tetra- n -alkylammonium halides dissociate phycocyanin, a protein that exists in solution as several well characterized aggregates. Hydrophobic interactions between the hydrophobic part of protein and bulky alkyl groups on R 4 N + ions play an essential role in inhibiting aggregation properties of this protein. , In view of increasing biological, pharmaceutical, and food applications, we have undertaken a systematic study of volumetric and rheological properties of some saccharides and their polyols in pure water and in Et 4 NBr (aq) solutions.…”
Section: Introductionmentioning
confidence: 99%